KEBIJAKAN PIMPINAN PONDOK PESANTREN DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN - Eko Budiywono; Yunus yunus (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This research is directedat 2 main things, namely: (1) How is the development of educational institutions at the Mambaul Huda Sumberurip Siliragung Islamic boarding school in Banyuwangi. (2) Whatis the policy of the pesantren leadership in develop ing educational institutionsat the Mambaul Huda Sumberurip Siliragung Islamic boarding school, Banyuwangi. This study us esqualitative methods as for there a son for using qualitative methods because in this study, researchers are at the same time an instrument in collecting data on leadership policies in develop ing educational institutions, so that researcher shave a method that has a very largerole, because what happened during the study needed a description. more in report writing. From the data obtained and the analysis carried out, it can be concluded that: (1) The development of educational institution satthe Mambaul Huda Islamic boarding school has been quite developed from previous years duet ot hein creasing number of students. (2) The policy of the pesantren leadership in develop ing educational in stitutionsat the Mambaul Huda Islamic boarding school, which still maintains traditional religious learning.